2018
DOI: 10.1002/acr.23528
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Against the Current: A Qualitative Review of the Work Experiences and Adaptations Made by Employees With Arthritis

Abstract: Arthritis disrupts an employee's work life by impairing his or her capacity to be a productive worker. Our results highlight how employees with arthritis make strategic adaptations to maintain a productive work life for as long as possible. The findings of this study have implications for work-related interventions aimed at preserving employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Our observations are consistent with those of Purc-Stephenson et al [ 21 ], who conducted a systematic review of 17 qualitative studies involving 873 workers with chronic inflammatory arthritis. Their study revealed 11 themes reported by employees with IA.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are consistent with those of Purc-Stephenson et al [ 21 ], who conducted a systematic review of 17 qualitative studies involving 873 workers with chronic inflammatory arthritis. Their study revealed 11 themes reported by employees with IA.…”
Section: Discussionsupporting
confidence: 93%
“…Important factors in disclosure include the need for an accommodation and having a supportive supervisor relationship (Munir et al, 2005;Schrader et al, 2014). However, other factors, such as knowing that an employer has made an effort to create a disability-friendly workplace, knowing that an employer was actively recruiting people with disabilities, knowing of employees who had disclosed and were successful, inclusion of disability in the diversity statement, knowing that disclosure could potentially pave the way to new opportunities for promotion or training, seeing a message of disability inclusiveness on the company's materials, seeing employees with disabilities at recruitment events, and employers having a disability-focused employee resource group (ERG), can also play a role in an individual's willingness to disclose and seek accommodations (Purc-Stephenson, Dostie, & Smith, 2018;Schrader et al, 2014).…”
Section: Stigma Identity and Disclosurementioning
confidence: 99%
“…The Job Sustainability Model, proposed for employees with arthritis, is organized in terms of three main aspects: personal factors, self-assessment and information gathering, and job sustainability strategies (Purc-Stephenson et al, 2018). In this model, an individual experiences a trigger event that causes them to engage in self-assessment and information gathering.…”
Section: Conceptual Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors not observed in this study such as having more seniority/job tenure could also provide the individual with a greater level of credibility, which in turn would make disclosure easier. However, disclosure is also an issue reported by adults who develop arthritis whilst employed [27], [28], [29], [30]. Prospective studies to further understand career trajectories of young people with arthritis will be of interest.…”
Section: Discussionmentioning
confidence: 99%